The landfill of early Roman Jerusalem the 2013-2014 excavations in area D3 - Gadot, Yuval (Ancient Jerusalem publications series, 2022)
"Presents the results of excavations at a landfill outside the walls of Jerusalem dating from the 1st century CE that functioned as the final resting spot of the discarded items of the city. The findings reveal city life shaped by halakhic rules of purity"--